Influence of Fundamental Factors on Dividend Payout Policy: Study on Construction Companies Listed on Indonesian Stock Exchange - Rico Eka Wahyu Hudiwijono; Siti Aisjah; Kusuma Ratnawati (Wacana Journal of Social and Humanity Studies, 2018)
This study examines the fundamental factors that influence the dividend payout policy, namely leverage, liquidity, free cash flow, firm size, firm growth, business risk and profitability. Several previous research results indicate differences in research findings. This study was conducted on five construction contractor companies listed in Indonesia Stock Exchange during 2010 to 2016. Multiple regression analysis was operated through SPSS 20 program and hypoteses testing simultaneously with F-test and partially with t-test. The results show that all independent variable are important factors in dividend payout policy, and firm size is the most dominant factors affecting dividend payout policy.Â